Reviewing Complex Static-Dynamic Concepts of Spine Stability: Does the Spine Care Only to Be Stiff to Be Stable? - Mahato, Niladri Kumar (Journal of Morphological Sciences, 2019)
Background Changes in the load-displacement relationship in spine segments suggesting alterations in biomechanical stiffness may not yield significant clinical information. Changes in Spine stiffness may arise secondary to neuro-muscular adjustments in the para-spinal muscles and may not be associated with physical anatomical laxity or motion restrictions at segmental articulations. Segmental stiffness may vary dynamically at different zones within the range-of-motion, suggesting a non-linear load-displacement relationship during motion. There is no linear, mechanistic relationship between spine pain and biomechanical markers of spine instability.Objective To review diagnostic assessment approaches of spine instability based on palpatory techniques, end-of-range radiography and imaging in light of our current understanding of biomechanical spine stability.Method The Medline and PubMed databases were screened for primary medical and engineering research articles and reviews on spine stability. Information related to bio-mechanical concepts and clinical decision-making were extracted and synthesized. Spine stability was described in two classical forms, the structural (anatomical) and the functional (physiological), the implications of static and dynamic instability was described in terms of biomechanical and mathematical models used to understand etiology of non-specific back pain.Results Evidence supports the view that dynamic adaptations in the load-displacement relationship of the spine may be resistive or assistive, depending on task-specific movements. Diagnosis of instability is based on structural and functional integrity of the segments in a static or dynamic context.Conclusion Development of specific criteria to define clinical spine stability, compatible with system-based biomechanical concept of spine stiffness, is an ongoing topic in clinical and basic science research.
Keywords: spine stability; load-displacement; stiffness; low back pain; para-spinal; motor-control